Functional MgO–Lignin Hybrids and Their Application as Fillers for Polypropylene Composites - Grząbka-Zasadzińska, Aleksandra; Klapiszewski, Łukasz; Jesionowski, Teofil; Borysiak, Sławomir (Molecules, 2020)
Inorganic–organic hybrids are a group of materials that have recently become the subject of intense scientific research. They exhibit some of the specific properties of both highly durable inorganic materials (e.g., titanium dioxide, zinc) and organic products with divergent physicochemical traits (e.g., lignin, chitin). This combination results in improved physicochemical, thermal or mechanical properties. Hybrids with defined characteristics can be used as fillers for polymer composites. In this study, three types of filler with different MgO/lignin ratio were used as fillers for polypropylene (PP). The effectiveness of MgO-lignin binding was confirmed using Fourier transform infrared spectroscopy. The fillers were also tested in terms of thermal stability, dispersive-morphological properties as well as porous structure. Polymer composites containing 3 wt.% of each filler were subjected to wide angle X-ray diffraction tests, differential scanning calorimetry and microscopic studies to define their structure, morphology and thermal properties. Additionally, tensile tests of the composites were performed. It was established that the composition of the filler has a significant influence on the crystallization of polypropylene—either spherulites or transcrystalline layers were formed. The value of Young’s modulus and tensile strength remained unaffected by filler type. However, composites with hybrid fillers exhibited lower elongation at break than unfilled polypropylene.